2008
DOI: 10.1080/17453670810016948
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic bone graft substitute with equine bone protein extract is comparable to allograft in terms of implant fixation: A study in dogs

Abstract: Background and purpose We studied whether osseointegration and fixation of plasma-sprayed titanium implants grafted with β-TCP granules (Ossaplast) can be improved by adding an osteogenic signal (Colloss E). The results were compared to implants grafted with fresh frozen morselized allograft with and without the Colloss E device.Methods 4 porous-coated Ti implants were placed in the proximal humeri in each of 10 dogs. All implants were surrounded by a 2.5-mm defect, which was grafted with: (A) β-TCP, (B) β-TCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…The smallest quantity of bone formation was found in the group HAP/TCP/CS 30:60:10, which indicates that the bone extract was absorbed deep into the scaffold during implant preparation, and the released quantity of bone proteins was too low to induce bone formation. These results support those from previous studies that showed that the formation of new bone depends on a ceramic content with a high HAP/TCP ratio and a high dose of bone proteins [5,9]. Furthermore, this study confirms that the presence of bioactive components reduced fibrous tissue formation and increased bone formation surrounding the inorganic scaffolds [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The smallest quantity of bone formation was found in the group HAP/TCP/CS 30:60:10, which indicates that the bone extract was absorbed deep into the scaffold during implant preparation, and the released quantity of bone proteins was too low to induce bone formation. These results support those from previous studies that showed that the formation of new bone depends on a ceramic content with a high HAP/TCP ratio and a high dose of bone proteins [5,9]. Furthermore, this study confirms that the presence of bioactive components reduced fibrous tissue formation and increased bone formation surrounding the inorganic scaffolds [9].…”
Section: Discussionsupporting
confidence: 91%
“…Tricalcium phosphate (TCP) has been shown to be a useful carrier for recombinant human BMPs (rhBMPs) and demineralized bone matrix (DBM) [7,8,9]. TCP has many positive features for use in in vivo implants, such as resorption rates closely matching the course of normal cancellous bone remodeling and that it can bond directly to bone and has a primarily osteoconductive nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A canine study demonstrated that fibrous tissue covered β-TCP implants, which hindered implant degradation and new bone formation. β-TCP in combination with BPE was protected from this phenomenon and gave a two-fold increase in mechanical implant fixation [71]. Some authors observed a synergistic effect between BPE and carboxymethylcellulose (CMC), where they reported that a 3% CMC gel could act as carrier or bulking agent either in gel or lyophilized form [28,69].…”
Section: Combination Of Other Materialsmentioning
confidence: 99%
“…Therefore, bone graft substitutes must be used and they should have good biocompatibility with the new prosthesis. Fortunately, Baas et al [71,79,95] thoroughly studied the biocompatibility of BPE for bone repair. They designed porous-coated titanium alloy implants, which they combined with different kinds of bone substitute material, and placed the implants in the lateral proximal humerus of dogs.…”
Section: Artificial Joint Revisionmentioning
confidence: 99%